How to deal with Anxiety Bibliometric Analysis in Islamic Perspective - Mukarrami, Nur Fadhillah; Syahidin, Syahidin; Sumarna, Elan (Universitas Muhammadiyah Metro, 2024)
This study provides a bibliometric review of research on anxiety treatment based on Islamic perspectives, which involves a systematic search in various Scopus databases visualized with VOSviewer, then analyzed and evaluated based on country bibliographic pairs, institution bibliographic pairs, journal bibliographic pairs, and co-occurrence of author/topic keywords. A total of 357 relevant studies were then analyzed and selected following the criteria of studies in the last ten years (2014-2024). The statistical analysis was applied to examine the bibliometric data produced through the investigation, identification, and extraction procedures. The results showed that the United States (based on country bibliography pairs), Department of Psychology (based on agency bibliography pairs), and Frontiers in Psychology (based on journal bibliography pairs) became the most influential in the discussion of anxiety and how to handle it from an Islamic perspective. Anxiety, religion, and depression are keywords that often appear in this field.